ANALISIS KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN WHOLESALE - Aliffia Putri Pradani; Dhani Ichsanuddin Nur; Ira Wikartika (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
The company value is a condition that has been achieved by a company which is a picture of public trust in the company after going through all the process of activities for several years. The purpose of this research is to obtain information and analyze the influence of profitability, liquidity and leverage which are several factors in influencing the value of wholesale companies listed on the Indonesia Stock Exchange for the period 2016 – 2019. The population in this study is all wholesale companies listed on the Indonesia Stock Exchange. Sampling method in this study using purposive sampling that is sampling with certain criteria that have been set. Wholesale companies sampled in this study as many as 18 companies. In this study using multiple linear regression analysis methods and classical assumption test with SPSS. The results obtained in this study are profitability and leverage has an influence on the value of wholesale companies while liquidity does not affect the value of wholesale companies. The company value is a condition that has been achieved by a company which is a picture of public trust in the company after going through all the process of activities for several years. The purpose of this research is to obtain information and analyze the influence of profitability, liquidity and leverage which are several factors in influencing the value of wholesale companies listed on the Indonesia Stock Exchange for the period 2016 – 2019. The population in this study is all wholesale companies listed on the Indonesia Stock Exchange. Sampling method in this study using purposive sampling that is sampling with certain criteria that have been set. Wholesale companies sampled in this study as many as 18 companies. In this study using multiple linear regression analysis methods and classical assumption test with SPSS. The results obtained in this study are profitability and leverage has an influence on the value of wholesale companies while liquidity does not affect the value of wholesale companies.